Determinación espacial de la distribución de la Eichornia Crassipes “Jacinto de Agua” en las fuentes de aguas lóticas ubicadas en la margen derecha del río Mayo. - Lozano Lozano, Cinthya (2010)
The right bank of the Mayo River has permanent tax, within which lies the Black River, Romero and Tioyacu, rivers that were identified and prioritized for the present study, the same ones that have their own similar characteristics for successful application design statistic used. Eichhornia crassipes floating species studied "Water Hyacinth" presents submerged roots, no apparent stem, provided with a rhizome, very special, consequential, from which a rosette of leaves that have a significantly inflated spongy surface shaped balloon that opens forming a bladder filled with air, whereby the plant can remain on the water surface and high reproductive capacity in water bodies mainly lentic. For this evaluation was hypothesized that the species Eichhornia crassipes "Water Hyacinth" is distributed in Romero, Black and Tioyacu rivers. Its comparison field was oriented by goals such as determining the spatial distribution in the rivers above through the zoning of the main sources of water, determining the percentage of the spatial distribution and identification of the biometric characteristics of the species under study. As a result it was determined that the spatial distribution of Eichhornia crassipes "Water Hyacinth" in Rios Romero, Black and Tioyacu, are at a height between 822 and 840 meters, in the case of the Black River is found at coordinates UTM: 249611 X, Y 9,332,666 (Item No. 16) at 2000 meters from the bridge carrozable cement road leads us to the village of San Vicente; in Romero river is found in the UTM coordinates: X 249880, Y9332679 (Point Nº05) up to the population center of Tamboyacu and the Tioyacu River is found in the UTM coordinates: X 246541, and 9338263 (Point Nº02) to height of the concrete bridge that leads to the Recreation Ecotourism Tioyacu. The spatial distribution of Eichhornia crassipes "Water Hyacinth" reaches 100% of the mirror surface of the water to the height of Fernando Belaunde Terry highway (as Artificial Benchmark Runner), this percentage remains constant until May River . Their presence is also associated with decreased height, speed and temperature increase, and especially in the presence of surfaces with established populations. The external physical conditions (T ° C, Altitude), chemical (pH), among other properties determining influence on the spatial distribution of Eichhornia crassipes "Water Hyacinth", the species needs low water velocities, lower altitudes near 20 Tº and 23 ° C, and amorphous bodies of water; the study area has populations mostly by not having sewer systems make wastewater, solid and sanitary waste is derived sources of water through surface runoff stormwater product mainly rainfall; Moreover the area is dominated by rice cultivation modern irrigation which suggests the inclusion of high percentages of nitrogen, phosphorus and sulfate components main products for optimal development and retention in water bodies. All this is causing the deterioration of aquatic ecosystems, because of the coating of the mirror surface of the water, the luminous efficiency decreases in the water source, to obstruct the passage of sunlight, which leads to the reduction of the content of oxygen and productivity. The presence of phytophagous and carnivorous animals in these aquatic plants presupposes the growth of infectious vectors and the loss of the navigability of water bodies by high population densities of Eichhornia crassipes "water hyacinth" impede the efficient use as transport.